Detection of response to chemotherapy using positron emission tomography in patients with oesophageal and gastric cancer - Graeme Couper; Dympna McAteer; F. Wallis; M. Y. Norton; A. Welch; M. Nicolson; K G M Park (1998)
Abstract Background The aim of the study was to determine whether 2-[18F]-fluoro-2-deoxy-d-glucose (FDG)-positron emission tomography (PET) could detect response to chemotherapy in patients with oesophageal and gastric cancer. Methods Fourteen patients underwent imaging before and after chemotherapy using FDG-PET. Computed tomography (CT), dysphagia scores and weight changes were used for comparison of evidence of response. Tumour to liver ratios (TLRs) and influx constants for FDG (K) were used for quantification purposes. Results Thirteen of 14 lesions were successfully imaged before therapy. Changes were seen in all follow-up scans, ranging from a complete response to a 15 per cent increase in tumour FDG uptake. Response was demonstrated by CT in four patients; all four had large reductions in FDG uptake after chemotherapy. Two patients with an increase in FDG uptake reported no improvement in dysphagia and continued to lose weight during therapy. Conclusion Changes in tumour FDG uptake were seen in all tumours after chemotherapy. FDG-PET may have a role to play in the assessment of patients with upper gastrointestinal malignancy receiving chemotherapy.